Site‐Controlled Single‐Photon Emitters Fabricated by Near‐Field Illumination. Issue 21 (2nd April 2018) - Biccari, Francesco; Boschetti, Alice; Pettinari, Giorgio; La China, Federico; Gurioli, Massimo; Intonti, Francesca; Vinattieri, Anna; Sharma, MayankShekhar; Capizzi, Mario; Gerardino, Annamaria; Businaro, Luca; Hopkinson, Mark; et al.
Abstract: Many of the most advanced applications of semiconductor quantum dots (QDs) in quantum information technology require a fine control of the QDs' position and confinement potential, which cannot be achieved with conventional growth techniques. Here, a novel and versatile approach for the fabrication of site‐controlled QDs is presented. Hydrogen incorporation in GaAsN results in the formation of N–2H and N–2H–H complexes, which neutralize all the effects of N on GaAs, including the N‐induced large reduction of the bandgap energy. Starting from a fully hydrogenated GaAs/GaAsN:H/GaAs quantum well, the NH bonds located within the light spot generated by a scanning near‐field optical microscope tip are broken, thus obtaining site‐controlled GaAsN QDs surrounded by a barrier of GaAsN:H (laterally) and GaAs (above and below). By adjusting the laser power density and exposure time, the optical properties of the QDs can be finely controlled and optimized, tuning the quantum confinement energy over more than 100 meV and resulting in the observation of single‐photon emission from both the exciton and biexciton recombinations. This novel fabrication technique reaches a position accuracy <100 nm and it can easily be applied to the realization of more complex nanostructures. Abstract : A novel and versatile approach for the postgrowth fabrication of site‐controlled quantum dots is presented. Starting from a GaAs/GaAsN:H/GaAs quantum well, H is removed by breaking the NH bonds with a near‐field light spot, thus obtaining site‐controlled GaAsN QDs surrounded by a barrier of GaAsN:H (laterally) and GaAs (above and below). This novel fabrication technique has a position accuracy <100 nm.